ONTOLOGY-BASED DATA WAREHOUSE VISUALIZATION USING PROTÉGÉ FOR CORONA VIRUS SPREAD INCIDENCES - Tazkia S Ardan; Denada Zahra; Meinawati Meinawati (Jurnal Teknologi Informasi dan Komunikasi, 2022)
Corona Virus (Covid-19) is an infectious disease caused by a newly discovered coronavirus. At this time, there are no specific vaccines or treatments for COVID-19. death rates due Covid-19 in Indonesia reach 8,9%. The presence of differences between data released by the Covid-19 complaint website of West Java Province and data released by Subang Government indicates that’s still difficult to obtain accurate information. We need to build data warehouse and create ontology of Covid-19 incidences data to figure out the important information in Covid-19. we are using Protégé to build and visualize ontology of Covid-19 data. Keywords : ontology, Protégé, Covid-19